Examining program quality in a national junior golf development program - Kramers, S.; Camiré, M.; Bean, C. (International Sport Coaching Journal, 2020)
Golf Canada recently restructured its national junior golf development program, Learn to Play, going from an original curriculum that focused on teaching golf skills to an updated curriculum that integrates the teaching of golf and life skills. The purpose of the study was to examine whether there were differences in program quality through implementation of the original program compared with the updated program. Five coaches using the original program and nine coaches using the updated program took part in the study over an entire summer golf season. The 14 coaches (Mage=40 years) were each systematically observed on three occasions (i.e., total of 42 observations) and completed an end-of-season program quality questionnaire. The data were subjected to descriptive statistical analyses. Results demonstrated that (a) coaches who implemented the updated program were observed fostering higher levels of program quality than coaches who implemented the original program and (b) researcher observation scores were significantly lower than coach questionnaire scores of program quality. Results are discussed to situate the influence of the updated program on markers of quality. Practical implications for coach education and explicit life skills curricula are discussed.